Extramedullary Plasmacytoma of the Third Eyelid in a Cat - Alves, Amanda de Deus Ferreira; Brito, Fábio Luiz da Cunha; Pereira, Márcia de Figueiredo; da Silva Junior, Valdemiro Amaro (Acta Scientiae Veterinariae, 2021)
Background: Extramedullary plasmacytoma is a neoplasm originating from plasmacytes with benign behavior, although it can present malignant characteristics such as local invasion and metastases in some cases. Primary extramedullary plasmacytoma in the third eyelid is rare in humans and animals and has not yet been described in cats. Thus, the goal of the present study is to describe the cytological and histopathological findings of an extramedullary plasmacytoma in a cat’s third eyelid. Case: A 5-year-old female feline patient with a history of ocular alteration for approximately 30 days was referred to the ophthalmology service. Upon ophthalmic examination of the left eye, an increase in volume with tissue proliferation was identified in the third eyelid’s conjunctiva. A collection of material for cytopathological examination was performed. Numerous plasmocytes and atypical lymphocytes with anisocytosis and anisokaryosis were observed, with a possible neoplastic injury being suggested and referred to the patient for surgical removal of the third eyelid. In the histopathological analysis, it was possible to observe several plasma cells and vascular neoformation along the entire conjunctive margin below the epithelium. The glands, serous and mucous, present in the fragment, revealed areas of intervening plasmacytic infiltrate and a large area close to the hyaline cartilage containing intense plasmacytic inflammatory infiltrate with rare neutrophils and macrophages. There was also a structural breakdown of glandular components and lymphocyte cells with mitosis figures and discrete cellular pleomorphism. Discussion: Plasmacytoma is a rare neoplasm in both dogs and cats. The anatomical regions most frequently affected are the digits, lips, and pinna. Concerning the 3rd eyelid tumor involvement, numerous types of neoplasms have been reported in dogs in the veterinary literature, including transmissible venereal tumor, squamous cell carcinoma, and melanocytoma melanoma, lymphoma, plasmacytoma, hemangioma, hemangiosarcoma, mastocytoma, and myoepithelioma. In cats, the third eyelid is the third site most affected by primary tumors. Adult and elderly animals are the most affected; however, an extramedullary plasmacytoma (PEM) has been reported in an eight-month-old male cat’s skeletal muscle. Plasmacytoma aspirates, like other round cells, tend to be highly cellular, the cell morphology has a plasmacytoid aspect, resembling mature cells, the cytoplasm is intensely basophilic, and the round nucleus with an eccentric disposition has thin chromatin and indistinct nucleolus. Binucleate and multinucleate cells are common, and the absence of lymphoglandular corpuscles helps differentiate extramedullary plasmacytoma from lymphomas. Histologically, PEM is similar in dogs, humans, and felines, and variations in mature and immature plasma cells can be seen. The diagnosis of extramedullary plasmacytoma is fundamentally histological, and immunohistochemical analysis can also be performed. Surgical excision with safety margins is the primary type of treatment for neoplasms in the 3rd eyelid, being considered an effective method, as seen in this report, during the patient’s follow-up for 13 months, no recurrence or metastasis of the neoplasm was seen. When signs of malignant neoplasms are found, it is recommended to evaluate the indication for chemotherapy before surgery and monitor the case after treatment due to recurrence risk.